Analysis of the Impacts of Health Cost and Risk Preference on Farmers' Protective Behavior of Pesticide Application Based on the Autoregressive Threshold Model: A Case Study of Wuhu City in China. (25th September 2022) - Cai, Shukai; Gu, Yaxing; Li, Runze; Teng, Zhonghong
Abstract : This paper is aimed at investigating the impacts of health cost and risk preference on farmers' protective behavior of pesticide in a case study of Wuhu city in China. Based on the field survey data from 523 farmers in the main grain-producing areas, the cost of illness (COI) method was employed to quantitatively measure the health cost (HC) of pesticide application, the Likert scale was used to measure the risk preference (RP) of pesticide applicators, and the autoregressive threshold model was used to test the impact of health cost and risk preference on farmers' protection behavior in the process of pesticide application. The key findings of this research case study reveal that when the health cost and risk preference are both lower than the critical value (HC ≤ 107.235, RP ≤ 3 ), the health cost does not affect improving the protection level of farmers in the process of pesticide application. However, when the risk preference exceeds the critical value (RP > 3 ), and the health cost exceeds a certain critical value (HC > 107.235 ), they have a significant positive effect on improving the protection level of farmers in the process of pesticide application. High health cost combines with higher risk preference (HC > 107.235, RP > 3 ) which can significantly improve the protection level of farmers in the process of pesticide application.